Motor Imagery: A Resource in the Fatigue Rehabilitation for Return-to-Work in Multiple Sclerosis Patients—A Mini Systematic Review - Agostini, Francesco; Pezzi, Letizia; Paoloni, Marco; Insabella, Roberta; Attanasi, Carmine; Bernetti, Andrea; Saggini, Raoul; Mangone, Massimiliano; Paolucci, Teresa (Frontiers in Neurology, 2021)
Fatigue is a multidimensional symptom with both physical and cognitive aspects, which can affect the quality of daily and working life activities. Motor Imagery (MI) represents an important resource for use during the rehabilitation processes, useful, among others, for job integration/reintegration, of neurological pathologies, such as Multiple Sclerosis (MS). To define the effective rehabilitation protocols that integrate MI for the reduction of fatigue in patients with MS (PwMS), a literary review was performed through August 2020. Five articles were included in the qualitative synthesis, including 2 feasibility pilot randomized control trials (RCTs) and 3 RCTs with good quality according to the PEDro score and a low risk of bias according to the Cochrane Collaboration tool. The literature suggested that MI, in association with rhythmic-auditory cues, may be an effective rehabilitation resource for reducing fatigue. Positive effects were observed on perceived cognitive and psychological fatigue. PwMS require greater compensatory strategies than healthy individuals, and the use of rhythmic-auditory cues may be useful for optimizing the cognitive processing of MI, which acts as an internal stimulus that is enhanced and made more vivid by outside cues. These findings provide evidence that MI is a promising rehabilitation tool for reducing fatigue in PwMS and return to work strategies..